EARLY DETECTION OF CHILD DEVELOPMENT AND GROWTH AGES 3-72 MONTHS IN CIHIDEUNG, TASIKMALAYA CITY - Irawan, Gusthine Almeera; Nabila, Alfika; Anis, Nur; Annisa, Maulida Nur; Saputri, Ririn Oktaviani; Qonita, Qonita (HEARTY, 2025)
Early childhood is a critical period of rapid development encompassing physical, cognitive, emotional, social, and sensory functions. This study aims to provide an overview of the growth and development of children aged 3 to 72 months in the Cihideung District, Tasikmalaya City. A descriptive qualitative approach with an observational design was employed. The study involved 30 children selected based on age criteria and parental consent. Data collection techniques included direct observation, anthropometric measurements, completion of the Pre-Screening Developmental Questionnaire (KPSP), and visual and auditory function assessments for children aged 4 to 6 years. The results indicate that most children were developing in accordance with their expected developmental milestones. A small proportion of children required further attention to ensure optimal development. In terms of growth, the majority of children demonstrated good nutritional status, although a few cases of height or weight not aligning with standard references were observed. Sensory assessments revealed that some children experienced difficulties with vision or hearing. These findings highlight the importance of regular early detection efforts and the active involvement of both families and professionals.